Aerospace series. Cables, electrical, for general purpose, single and multicore assembly. XLETFE Family. Jacketed or screened and jacketed. Tin plated copper. Operating temperatures, between 65 °C and 135 °C. Single extruded wall for open applications, with jacket without screen. UV laser printable. Product standard Part 003, (6th September 2019) - British Standards Institution,
No abstract available